Composition of the compounds bonded via ether, ester and sulfide linkages in oils of natural bitumen from Ashalchinskoye deposit - Vladimir Antipenko; Tatyana Cheshkova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The urgency of the discussed issue is caused by the necessity to obtain and summarize the information on composition and structure of oily and resin-asphaltene components from unconventional hydrocarbon sources - heavy high-viscosity oils and natural bitumen, to solve the problem of their production, transportation and processing, as well as rational use of the products obtained. The main aim of the study is to establish compositions and structures of molecular fragments in oily components bonded via oxygen and sulfur in petroleum and natural bitumen. The methods used in the study: chemical reactions of ether and ester bonds ruptures using BBr3, reduction of the formed bromides with lithium alumohydride, reactions of C-S bond destruction in aliphatic and saturated cyclic fragments of oil sulfide molecules, methods of IR-Fourier-, NMR 1 Н and gas chromatography-mass spectrometry. The results: It was shown for the first time that alkyltrimethyl benzenes, alkylcyclohexanes, сheilanthanes, hopanes and phenanthrenes occur in oils of heavy high-viscosity maltha of Ashalchinskoye deposit not only in molecular but also in the "bonded" forms in the components of the so-called "unresolved complex mixture". The alkyltrimethyl benzenes and alkylcyclohexanes are bonded with other structural fragments both via ether, ester and sulfide linkages. The changes in cheilanthanes, hopane and phenanthrene compositions are observed only after the destruction of sulfide bridges. Therefore only "sulfur-bonded" form is typical to these compounds.